Epidemiological aspect of scorpion sting in Bandar Abbas, Iran, during 2009–2011 - Moosavy, Seyed Hamid (Electron Physician, 2016)
INTRODUCTION: People in tropical and semi-tropical areas are in danger of scorpion sting, and this can be a serious problem for them. Mortality due to scorpion sting in the tropical and semi-tropical areas of Iran is about 75%, and this makes scorpion sting in these areas a serious medical problem. Because of this problem, our aim was to assess the epidemiological aspects of scorpion sting in Bandar Abbas, Iran, during 2009–2011. METHODS: In this cross-sectional retrospective study, epidemiologic data of 698 scorpion sting cases, who were referred to the Shahid Mohamadi Hospital of Bandar Abbas in Hormozgan Province collected from 2009 until 2011. The data included demographic and individual information, such as age, gender, geographic location, bite site, when the incident occurred, and anti-venom consumption. The required data were extracted from the patients’ recorded information in the Hospital, and we recorded data in a special checklist and imported the data into the computer for statistical analysis using of SPSS software, version 21.0. Descriptive statistics, including mean, standard deviation, frequency, and percentage, were used for data analysis. RESULTS: Two hundred and sixty-one (37.4%) of the cases were urban and 437(62.6%) were rural. Males comprised 50.1% of the cases, and women comprised 49.9% (p >0.05). Twenty-five point two percent of scorpion sting cases occurred among people in the 21 to 30 age group, and there were very few cases among people in the 51 to 60 age range (p<0.05). Most of cases were recorded in April and October, and the fewest cases were recorded in July and January (p<0.05); also 32.2% of scorpion sting cases occurred after midnight and in the early morning hours. CONCLUSION: Our survey showed that there was a high incidence of scorpion stings in rural areas, among 21–30 age group, among housekeepers, and among students. These results indicate the need for public education programs and better sanitation services in the rural areas around Bandar Abbas city. Prospective studies can help to health and medicine organization for prevention and treatment of scorpion sting.